ANALISIS SAMPUL BUKU MATEMATIKA SD KELAS 1: ANALISIS SAMPUL BUKU MATEMATIKA SD KELAS 1 - Alun Matiti; Hariyanto S. Auna; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Textbooks are textbooks used by teachers and students in the learning process. In addition, textbooks are also one of the most needed tools in the scope of the school. Textbooks are books compiled by experts in accordance with a particular field of study. One of the textbooks arranged according to the field of study is the elementary school mathematics textbook for grade 1. The student book LEARN WITH YOUR FRIENDS MATHEMATICS FOR ELEMENTARY SCHOOL 1ST GRADE This is translated from the book STUDY WITH YOUR FRIENDS MATHEMATICS FOR ELEMENTARY SCHOOL, published by Gakko Tosho CO., LTD . In English. This book is then translated into Indonesian and goes through a long process so that it is in accordance with the learning outcomes of elementary school mathematics as well as the cultural context and everyday life in Indonesia. This book has been used at the elementary school level, especially grade 1, and has met the applicable curriculum standards. The research method used by researchers in this study is a qualitative approach in presenting descriptive data, from discussion to conclusions. The data analysis carried out by the researcher was to analyze the cover illustrations of grade 1 elementary school mathematics books to determine the relationship between the cover and the contents of the book and the feasibility of its use. . Overall, the research assesses the shape, color and illustration concepts used, so the cover design is very feasible to use. From the selection of colors, the forms of writing and illustrations that are used are very suitable so that they are very helpful and suitable for elementary school age students.